Hyperinflation in Venezuela, and its Financial Audit Effects (Global Journal of Management and Business Research, 1970)
This documentary research through activities carried out in Audit and Assurance II aims to identify problems studied in terms of effects of hyperinflation in Venezuela on financial audit processes analyzed by seventeen 17 Sixth semester students in the Public Accounting career at the Universidad Cat lica Andr s Bello developed during the months of October to December 2019 Among the most outstanding conclusions the fact that hyperinflation generates profound distortions in financial statements can be observed
Keywords: hyperinflation; audit; financial; venezuela